2018
DOI: 10.4103/ija.ija_566_17
|View full text |Cite
|
Sign up to set email alerts
|

Fast tracking in adult living donor liver transplantation: A case series of 15 patients

Abstract: Background and Aims:Fast tracking (FT) for more efficacious use of resources may be difficult after living donor liver transplantation (LDLT) due to a partial liver graft, complex vascular anastomoses and longer operating time. Our study was aimed at reporting our experience with FT (on table extubation) in LDLT recipients. A secondary objective of our study was to look at defining a subgroup of patients who could be prospectively planned for FT.Methods:We studied the demographics and outcomes of 15 LDLT recip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 13 publications
0
9
0
4
Order By: Relevance
“…There is also evidence that early extubation after OLT improves patient outcome and saves costs [17,18]. However this fast track approach needs to fulfil some important criteria, such as haemodynamic and respiratory stability, no expected graft dysfunction, no large intraoperative blood loss, normal pH, normothermia, uncomplicated surgery, and good teamwork between surgeons, anaesthesiologists and intensivists [39]. Obviously, complete recovery from NMB to avoid respiratory failure due to PORC is mandatory and rocuronium-sugammadex use provides a valid option, especially because extubation failure after surgery and the need for reintubation represent an important mortality risk factor [40].…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence that early extubation after OLT improves patient outcome and saves costs [17,18]. However this fast track approach needs to fulfil some important criteria, such as haemodynamic and respiratory stability, no expected graft dysfunction, no large intraoperative blood loss, normal pH, normothermia, uncomplicated surgery, and good teamwork between surgeons, anaesthesiologists and intensivists [39]. Obviously, complete recovery from NMB to avoid respiratory failure due to PORC is mandatory and rocuronium-sugammadex use provides a valid option, especially because extubation failure after surgery and the need for reintubation represent an important mortality risk factor [40].…”
Section: Discussionmentioning
confidence: 99%
“…17 Despite of the scarcity of studies and literature referring to reintubation predictor scores after LTx, Magalhães et al 18 observed that cold ischemia time, a variable used in the BAR score still in the intraoperative period, was a predictor of pulmonary complications after LTx. In view of the variables analyzed in the BAR score, Bhangui et al 19 observed that young patients with a low MELD value are viable and safe candidates to be extubated still on the operating room after LTx. Ferraz Neto et al 20 reported that patients after LTx with BAR values below 18 showed longer ICU stay for respiratory complications and survival below 80%, corroborating the findings of the current study, in which the BAR score showed good discriminating power through AUC in predicting reintubation and through multivariate analysis (OR = 1.18; 95%CI 1.02-1.36; p = 0.02).…”
Section: Discussionmentioning
confidence: 99%
“…When phenylephrine doses exceeded 500 µg, adrenaline was added in increments of 10 µg. We believed that blood pressure measurements from the femoral artery could reduce the vasopressors needed and provide scope for fast-tracking extubation,[ 9 ] but the mean pressures from both sites were found to be comparable.…”
Section: Discussionmentioning
confidence: 99%